Travel Nest - Ahmad Shaer; Arwa Maroof (My University, 2024)
During the Pandemic that started in the end of 2019 and continued for about three years most of people started relaying on online services to buy their grocery or to do business or to work. So, many more and more companies started to creating an online application for their services and started promoting their application through social media like Instagram, Facebook, Twitter etc. and most of the local business followed that pattern to keep up to the change. Our application is an online booking mobile application. That gives users the chance to visit the beautiful city of Palestine and its many landmarks and connect them with the closest hotel in that area in which they don’t have to spend much time on traveling and they can search for the closest hotel for their destination and also choose the range of prices they would like to spend and in addition to a recommendation system to give them a personalized experience. The hotel manager can edit the information and post images and add offers and manage the reservation that he gets. The application provides a feedback report to give the hotel manager an easy way to keep up with their customers ratings. The idea of Online booking has been done before but it has never been implemented in Palestine as far as we know and a booking application that contains almost all of the hotels available in Palestine in one site and a Recommendation system based on number of factors such as rating and pricing and location visited.